Past and present of large housing estates in Visegrad countries and Armenia - Erőss, Ágnes (Hungarian Geographical Bulletin, 2013)
In all Visegrad countries (the Czech Republic, Hungary, Poland and Slovakia), as well as in Armenia, a large proportion of the housing stock consists of blocks of flats erected during the Communist era. Those quarters have become an identical part of the cityscape inducing intense scientific discussion in the field of social sciences including human geography addressing such topics as architectural and spatial planning of housing estates, the analysis of society settled in those blocks of flats or even the psychological effects of the uniform environment on individuals. Following the systemic transformation the possible rehabilitation of the gradually deteriorating housing stock and environment meant a further challenge. Although examples from the West European countries provide significant help and information regarding housing estate rehabilitation, nevertheless due to the different scale of the problem, the altering history and the embeddedness of the topic, discussion on regional level is not only promising but necessary at the same time. This paper focuses on the important questions of large housing estates (LHEs) with special attention to the Visegrad countries and Armenia.